Development of Plant-Derived Antimicrobial and Cryoprotective Ingredients for Improving the Microbial Safety and Quality of Frozen Dough Products - Keartik Ray; Qianchun Xue; Dylan Mills (International Journal of Clinical and Translational Medicine, 2026)
Frozen dough products constitute a rapidly growing segment of the global bakery market, yet they remain vulnerable to microbial contamination and structural deterioration caused by ice recrystallization during storage and distribution. The shift toward clean-label products has intensified interest in plant-derived bioactive compounds that can simultaneously inhibit spoilage and pathogenic microorganisms while preserving the rheological and baking performance of dough under frozen conditions. This paper presents a systems-level analysis of the development, integration, and governance of plant-based antimicrobial and cryoprotective ingredients for frozen dough applications. We conceptualize the ingredient development process as a socio-technical infrastructure that spans agro-ecological sourcing, green extraction technologies, formulation engineering, and supply chain integration. Through this lens, we examine structural trade-offs among antimicrobial efficacy, cryoprotective functionality, sensory impact, and cost-effectiveness. The paper explores the architecture of distributed biomass supply networks, the resilience and robustness of bioactive performance under variable processing and cold-chain conditions, and the fairness implications of transitioning ingredient portfolios toward plant-derived alternatives in diverse economic contexts. Further, we analyze regulatory pathways, standardization challenges, and sustainability assessments required to support large-scale deployment. By reframing ingredient innovation as an infrastructural challenge, we highlight the importance of modular design, adaptive governance, and lifecycle thinking in realizing safe, high-quality frozen dough products through plant-derived solutions. The analysis draws on recent advances in polysaccharide cryoprotectant design, polyphenol antimicrobial mechanisms, and circular bioeconomy models, offering a forward-looking perspective on how interdisciplinary coordination can accelerate the translation of laboratory discoveries into resilient food systems.